Development of cooperatives in the Republic of Moldova - Anatolie Ignat; Alexandru Stratan; Eugenia Lucasenco (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The paper presents the review of the development of cooperatives in the Republic of Moldova during the post independence period. After the massive land privatization a large number of small scale agricultural producers occurred that hardly can compete with large scale producers. This preserves a state of underdevelopment of small farmers and of the rural sector. To identify problems that jeopardize cooperation processes and potential solutions a study on the development of cooperatives in the country was carried out. The major problems and possible solutions were identified through a semi-structured survey that encompassed 150 agricultural producers purposively selected in North, Central and South regions of the country. Addressing this critical situation can be made by coagulating dispersed efforts of small scale farmers to reduce costs of purchasing agricultural inputs and services, improve the access to post harvest, processing, transportation, financing, consulting services. Access to more stable markets and negotiation of better prices and better conditions of delivery can also be achieved through consolidated efforts agricultural producers' groups.
Keywords: Q13; Q15; 330; agriculture; small scale agricultural producers; agricultural cooperatives; marketing groups